Two-Phase System for Generating a Higher-Frequency Rotating Magnetic Field Excited Causing Hyperthermic Effect in Magnetic Fluids - Andrzej Skumiel; Rafal M. Wojciechowski (Energies, 2022)
This article presents a new method of excitation for a fast-changing rotating magnetic field (RMF) of higher frequencies (HF) causing the hyperthermic effect in magnetic fluids. The method proposed here uses a magnetic field exciter (inductor) consisting of a ferrite magnetic circuit and a system of coils connected in a two-phase arrangement. The proposed system is powered by two higher-frequency rectangular signals, with a 90-degree phase shift between each other, through HF transformers with ferrite cores. This paper presents the outcomes of the operation of RMFs in the frequency range of 38 kHz to 190 kHz, with a value of amplitude of magnetic field intensity H equal to 20 kA/m and increasing temperature, in a sample of APG513 magnetic liquid. The obtained results show that, in the range of the magnetic field intensities of moderate values, at a constant frequency f, the values of the time derivative of temperature are proportional to the square of the magnetic field intensity dT/dt~H2. Moreover, the values of the temperature rate, which are measured with the constant value of the magnetic field intensity, are proportional to the square of the frequency dT/dt~f2. At higher amplitudes of the RMF, the relationship dT/dt~H2 is no longer fulfilled, and an inflexion point of this function appears. In the case of the highest values of the achieved intensity amplitudes (H = 20 kA/m), the parameter of the Langevin function achieves a value equal to ξ = 6.